Leveraging the value of conservation physiology for ecological restoration. (17th February 2022) - Tomlinson, Sean; Tudor, Emily P.; Turner, Shane R.; Cross, Sophie; Riviera, Fiamma; Stevens, Jason; Valliere, Justin; Lewandrowski, Wolfgang
Abstract : The incorporation of conservation physiology into environmental management, particularly ecological restoration, is underutilized, despite the capacity of such approaches to discern how populations respond to the challenges of unpredictable and potentially inhospitable environments. We explore several examples where detailed mechanistic understanding of the physiological constraints of keystone and foundational species, ecological service providers such as insect pollinators, and species of conservation concern has been used to optimize the return of these species to landscapes following the cessation of mineral extraction. Using such data can optimize the rapid return of functioning ecosystems during restoration or increase the conservation value of restoration by returning insurance populations of threatened species. Integrating this level of mechanistic understanding with fine‐resolution spatial data in the form of biophysical modeling can help plan recovery and identify targets that can subsequently be used in assessing restoration success, particularly in situations that require substantial investment over long periods, such as post‐mining restoration. There is growing recognition of the valuable insights offered by conservation physiology to broader practice and policy development, and there have been substantial technical developments in conservation physiology leading up to and into the twenty‐first century as a result. The global challenge facing restoration ecology has, however, also grown in that time. Rapidly and efficiently meeting ambitious global restoration objectives will require a targeted approach, and we suggest that the application of physiological data will be most strategic for rare species, keystone species, and ecosystem service providers more broadly.